MRNA NFATC1 EXPRESSION IN GENU OSTEOARTHRITIS WITH EFFUSION - Reagan, Muhammad; Hermansyah, Hermansyah; Hidayat, Rachmat; Darma, Surya; Muthia, Putri (Biomedical Journal of Indonesia, 2020)
Based on a study conducted by the WHO Global Burden of Disease in 2010 stated, OA ranks 11th, the cause of disability in the world, and ranks 6th in East Asia and the Asia-Pacific countries, ranked 10th in North America, ranked 7th in Eastern Europe , and ranked 13th in Western Europe. Pathogenesis of osteoarthritis (OA) as degenerative joint disease that was once thought caused by a mechanical process. The prevalence, etiology, pathogenesis and progression of OA are still not understood until now, mainly because of the many influencing factors. This type of research is a analytic study. It was conducted in Rheumatology Polyclinic Dr. Mohammad Hoesin Palembang from February to December 2019. Affordable research population is all genu osteoarthritis sufferers with effusion who go to Dr. RSUP Mohammad Hoesin Palembang as 80 samples. Comparison of NFATC1 mRNA levels in genu osteoarthritis patients with effusion shows that there is no difference in gender and history of diabetes, whereas hypertension history and degree of osteoarthritis based on Lawrence Kalgren shows significantly different expression of NFATC1 mRNA. Age with NFATC1 mRNA expression showed no significant correlation, in contrast to BMI, Stroke Test and joint effusion volume showed a weak significant correlation, even though the direction of the correlation was negative on Stroke Test and joint effusion volume.